Development of emotional sphere of teenagers with deviant behavior by means of music - Сидоренко, Тетяна Дмитрівна (Pedagogy of Higher and Secondary Education, 2013)
Sidorenko T. D. Development of emotional sphere of teenagers with deviant behavior by means of music. The article describes the possibility of using music as a means to develop the emotional sphere deviant adolescents, offered conditions which, in the author’s opinion are necessary for the implementation of emotional rehabilitation of teenagers by means of music.